Adat Sabat Sebatatn Banua Simpakng: Studi Komparasi Tradisi Lokal dan Perkawinan Gereja Katolik - Ranubaya, Fransesco Agnes; Krisnanda, Vincentius Septian; Endi, Yohanes (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2024)
This study analyzes the Sabat Sebatatn marriage custom in Banua Simpakng and compares it with the marriage ceremony in the Catholic Church through a literature study approach. Through in-depth analysis of relevant texts and literature sources, the research illustrates the essential differences between the two marriage systems. The Sabat Sebatatn custom in the local cultural context of Banua Simpakng emphasizes family and community togetherness in a series of rituals rich in meaning. Catholic Church marriage, on the other hand, is spiritually oriented with an emphasis on spiritual commitment between the couple. This comparison provides insight into how marriage customs and religion co-exist in shaping marriage norms in society. By integrating a qualitative perspective and desk research, this study provides a deeper understanding of the complex relationship between local traditions and global religion in the context of marriage.